The digital rights movement the role of technology in subverting digital copyright - Postigo, Hector (The MIT Press, 2012)
The evolution of activism against the expansion of copyright in the digital domain, with case studies of resistance including eBook and iTunes hacks.
Keywords: Copyright and electronic data processing.; Digital rights management.; Hacktivism.; Internet -- Law and legislation.; Piracy (Copyright) -- Prevention.; Fair use (Copyright); elektronické knihy; electronic books